The Influence of Leadership Style and Competency on Employee Performance with Motivation as an Intervening Variable in Suku Dinas Pendidikan Jakarta Utara II - Riyanti, Mita; Noerman, Teuku (Formosa Journal of Science and Technology, 2024)
The success or failure of an agency in achieving its goals can depend on the leadership style, competence, and motivation of employees at taking out the performance. The author researcher that this goal is to find out the influence of Leadership Style and also Competency variables on Employee Performance with Motivation that stated as Intervening Variables in the North Jakarta Education Office II Department. The method in this study used a questionnaire analyzer using SmartPls4. The results here that including 202 employees as subjects, a program that 1) there’s no positive and significant impact Ong the Leadership Style the Employee Performance, 2) there’s a significant positive impact among the Competency on Employee Performance, 3) a significant positive impact among Leadership Style on motivation, 4) a significant and positive impact among competence to the motivation, 5) a significant and positive impact among motivation to the employee performance, 6) a significant and positive impact among Leadership Style to the motivation, a significant and positive impact among competence to the Employee Performance by motivation.